The role of intermediaries in sectoral innovation systems: The case of Mongolian information technology sector - Dashdondov, Batkhuyag; Nergui, Sonintamir; Choimaa, Lodoiravsal; Ganzorig, Oyundari; Purevjav, Narantsetseg (Proceedings of the Mongolian Academy of Sciences, 2024)
This paper analyses the types of innovation intermediaries that have emerged in Mongolia and investigates their roles within the information technology sector of the country. The study finds that diverse innovation intermediaries have emerged, and the majority of the intermediaries are non-sector specific, with only a few specializing in a single industry. The sector-specific intermediary plays a crucial role in building linkages and providing access to resources in sectoral innovation systems in developing countries. The study identifies several constraints related to funding and innovation policy support for these intermediaries. Consistent policy and financial support for sector-specific intermediary organizations could strengthen their role in the developing countries, particularly those with limited human and capital resources, such as Mongolia. This study contributes to an important understanding of the roles of intermediaries in underdeveloped and newly developed immature innovation systems of developing countries with low income and limited resources. As for the innovation system of Mongolia, it is impending to strengthen the sector-specific intermediary organizations through government and budgetary support and training for specialized human resources. The study also provides valuable insights that can guide the future development of the industry.